Proximity marketing: background and best practices - Kato, Saul (Henry Stewart Talks, 2009)
What is proximity marketing?, Mobile content hotspots, How it works for the consumer, Types of deliverable content, Proximity technology, Bluetooth basics, Recipe for a successful Bluetooth campaign, Measurement and statistics, Detailed campaign report, Pricing models, New areas of innovation
Archived at 2022/04/11